2018
DOI: 10.1080/10790268.2018.1543094
|View full text |Cite
|
Sign up to set email alerts
|

Engaging in the prevention of pressure injuries in spinal cord injury: A qualitative study of community-dwelling individuals’ different styles of prevention in Switzerland

Abstract: Context: Spinal cord injury (SCI) is a complex chronic condition with multiple self-management requirements and a high prevalence of complications. Pressure injuries (PIs) are among the most common ones and represent a frequent reason for re-hospitalization. This study aimed to identify styles of prevention that individuals with SCI adopt to deal with the risk of developing PIs. Design: Qualitative explorative interview study. Data was collected through semi-structured interviews, which were transcribed verbat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 37 publications
2
22
0
Order By: Relevance
“…User personas are fictitious characters to represent different prospective user types who are characterized by specific goals and behaviors [ 35 ]. The user personas adopted for this study described the three different prevention types that had been identified in earlier work: the thoughtful, the selective, and the delegator [ 13 ]. Each prevention type is characterized by different preventive behaviors, knowledge, and attitudes toward the prevention of pressure injuries; collaboration with health care professionals; and attitudes toward spinal cord injury in general [ 13 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…User personas are fictitious characters to represent different prospective user types who are characterized by specific goals and behaviors [ 35 ]. The user personas adopted for this study described the three different prevention types that had been identified in earlier work: the thoughtful, the selective, and the delegator [ 13 ]. Each prevention type is characterized by different preventive behaviors, knowledge, and attitudes toward the prevention of pressure injuries; collaboration with health care professionals; and attitudes toward spinal cord injury in general [ 13 ].…”
Section: Methodsmentioning
confidence: 99%
“…The user personas adopted for this study described the three different prevention types that had been identified in earlier work: the thoughtful, the selective, and the delegator [ 13 ]. Each prevention type is characterized by different preventive behaviors, knowledge, and attitudes toward the prevention of pressure injuries; collaboration with health care professionals; and attitudes toward spinal cord injury in general [ 13 ]. For example, in one of the exercises, participants worked in smaller groups to create a list of app features and functionalities that would be perceived as “cool” or “not cool” by the respective type their group had been assigned.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Notwithstanding that preventative care is a collaborative effort amoung health professionals, caregivers and patients, the patient’s role and intrinsic influences in preventative care are important (Zanini et al 2019 , 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Patients’ activation (Greene & Hibbard 2012 ); outlook and control over personal care (Munce et al 2014 ); knowledge levels of SHCs; attitude to prevention care; belief in personal susceptibility and taking responsibility for personal well-being influence prevention care practice (King, Porter & Vertiz 2008 ; Zanini et al 2020 ). Moreover, belief in one’s ability to self-manage has been identified as an essential component of managing a chronic condition (Disler, Gallagher & Davidson 2012 ; McCorkle et al 2011 ).…”
Section: Introductionmentioning
confidence: 99%